A case of acute focal bacterial nephritis caused by methicillin-resistant Staphylococcus saprophyticus in a 13-year-old adolescent girl treated with daptomycin. (2022) - Kinoshita, Teruhisa; Sahara, Shoko; Mihara, Yuka; Asai, Yumiko; Sato, Hiroko; Sakakibara, Takashi; Takimoto, Norio; Oka, Keisuke
Abstract: Staphylococcus saprophyticus is a gram-positive, coagulase-negative member of the Staphylococcus genus and is second only to Escherichia coli as a cause of urinary tract infections in the young female population. S. saprophyticus usually has good susceptibility to drugs commonly used to treat urinary tract infections, but it is often methicillin-resistant. Here we report a case of acute focal bacterial nephritis in a 13-year-old female patient caused by methicillin-resistant S. saprophyticus and treated with daptomycin (DAP). The patient had a history of unilateral hearing loss and presented to her previous physician with a 3-day history of fever, right-sided abdominal pain, and diarrhea. Cefotaxime antimicrobial chemotherapy was initiated as an empiric therapy targeting E. coli, the most frequent cause of community-onset pyelonephritis. Vancomycin (VCM) was started for acute focal bacterial nephritis caused by methicillin-resistant S. saprophyticus but was stopped due to allergy and replaced with DAP. After 13 days of treatment with DAP, the patient received 17 days of treatment with sulfamethoxazole-trimethoprim combination therapy. The patient experienced no adverse events and did not relapse. DAP is a relatively new anti-methicillin-resistant Staphylococcus aureus drug used to treat gram-positive cocci infections. It is primarily excreted by the kidneys, which may be desirable in treating urinary tract infections. For children who cannot receive VCM for any reason, DAP may be a viable alternative. Highlights: S. saprophyticus is a common cause of urinary tract infections in young women. The use of daptomycin for urinary tract infections in children is rare. Vancomycin (VCM) is usually used to treat methicillin-resistant S. saprophyticus . If VCM is unavailable, daptomycin can used to treat urinary tract infections in such cases.